UNDERSTANDING MALE CAREGIVER BURDEN IN THE UNITED STATES: A NATIONAL STUDY. (11th November 2018) - Lopez-Anuarbe, M; Kohli, P
Abstract: Men represent an increasing percentage of unpaid family caregivers, now forty percent (AARP and NAC 2015). Men caregivers face caregiving burden and have weaker support networks compared to women, are less likely to seek out programs that help them cope with this burden and that increase their caregiving capabilities. This study uses 2011 and 2015 National Study of Caregiving (NSOC) data and hierarchical regressions to identify the emotional, financial, and physical burden of five different groups of male caregivers, and the need for support that reduces stress associated with caregiving based on their personal characteristics, caregiving responsibilities, and available resources. In contrast to previous studies that use small, non-random samples, we employ a nationally representative sample and two points in time to study how overwhelmed each sub-group is and whether they are using supportive services for caregivers. Results show that all groups reported multiple types of burden, particularly when engaging in certain tasks such as personal care. Though husbands bore the brunt of personal care, at times sons and sons-in-law reported higher levels of stress despite having stronger personal networks and seeking assistance more actively than husbands. Given the very low usage of caregiver support and training, it is necessary to devise, implement, and market effective policies that intentionally include gender, age, and cultural differences in order to encourage more caregiving and to relieve the stress of different groups of male caregivers in particular, and of all caregivers in general.